2010
DOI: 10.1103/physrevlett.105.067401
|View full text |Cite
|
Sign up to set email alerts
|

Fraction of a Millimeter Propagation of Exciton Polaritons in Photoexcited Nanofibers of Organic Dye

Abstract: We report propagation of exciton polaritons (EPs) in photoexcited nanofibers of thiacyanine dye over a few hundred micrometers at room temperature. We determine the complex refractive index along the nanofibers by fluorescence microscopy measurements on single nanofibers and observe its anomalous behavior due to the EP effect. The longitudinal-transverse splitting energy (ΔE(L-T)) is evaluated to be ∼1  eV. The large ΔE(L-T) and waveguide function of the nanofibers allow a millimeter propagation of EPs at room… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
258
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 151 publications
(270 citation statements)
references
References 20 publications
11
258
1
Order By: Relevance
“…Owing to the fact that Δ E L-T and E ex are much larger than kT at room temperature ( ∼ 30 meV), the EPs in the nanofi bers are suffi ciently stable to propagate over millimeter-scale distances at room temperature. We have also shown that that the refractive index n( λ ) of the nanofi bers ( λ : wavelength) increases dramatically with a decrease in λ and exceeds 10 near the transverse exciton energy, [ 11 ] suggesting that the EPs should be transmitted through a micrometer-scale bend in a nanofi ber.…”
Section: Micrometer-scale Photonic Circuit Components Based On Propagmentioning
confidence: 96%
See 3 more Smart Citations
“…Owing to the fact that Δ E L-T and E ex are much larger than kT at room temperature ( ∼ 30 meV), the EPs in the nanofi bers are suffi ciently stable to propagate over millimeter-scale distances at room temperature. We have also shown that that the refractive index n( λ ) of the nanofi bers ( λ : wavelength) increases dramatically with a decrease in λ and exceeds 10 near the transverse exciton energy, [ 11 ] suggesting that the EPs should be transmitted through a micrometer-scale bend in a nanofi ber.…”
Section: Micrometer-scale Photonic Circuit Components Based On Propagmentioning
confidence: 96%
“…Recently, we demonstrated that the mechanism of the active waveguiding is the propagation of EPs. [ 11 ] Such effi cient long-range EP propagation, which is rarely observed for other materials, is attributed to the high stability of the EPs in the nanofi bers. The stability of EP is determined by the magnitude of the longitudinal-transverse exciton splitting energy Δ E L-T and the exciton binding energy E ex with respect to thermal energy kT .…”
Section: Micrometer-scale Photonic Circuit Components Based On Propagmentioning
confidence: 98%
See 2 more Smart Citations
“…Another optical configuration that strongly confines photons, and therefore can be considered for strong coupling with excitons, is an optical waveguide. This configuration is both common and highly suitable for applications, but has received only modest attention in the context of strongly coupled modes [18][19][20][21]. Waveguide modes are advantageous compared to cavity modes since they can propagate, can be studied and directly probed at the near field through their evanescent tails and the devices can be deformed with little change to the modes of the system, in the same way that optical fibers can be bent with little effect.…”
mentioning
confidence: 99%